The Results of Using Games In Learning Process - Abdusalomova Aziza Xomidovna (International Journal on Integrated Education, 2023)
Among numerous sources of children’s interest in the language learning process, games seem to be very important. Obviously, there are a lot of other sources, such as pictures and stories. Pictures serve as a visual stimulus, while games use both visual and aural channels and activate language production and, sometimes, physical movement [2, 112].